MAIN DIRECTIONS OF USING DIGITAL TECHNOLOGIES IN TOURISM - Abdullaev Ravshan Vakhidovich (Scholar Express Journals, 2025)
This article examines the introduction of digital technologies in the tourism industry, which leads to wider dissemination of information about tourist sites, as well as the potential applications of 3D technologies in Uzbekistan's tourism sector. Furthermore, several examples illustrate the use of 3D modeling technologies for achieving various goals and objectives in the tourism sector. The advantages of 3D visualization, such as realistic images, interactivity, and marketing opportunities, are described. The article presents information about attractions in Spain and France, as well as 3D models of sacred sites in Saudi Arabia, as examples of international experience
Keywords: Tourism industry; 3D technologies; virtual reality